Cyclic durability of calcium carbonate materials for oxide/water thermo-chemical energy storage. (September 2019) - Uchiyama, Naoto; Takasu, Hiroki; Kato, Yukitaka
Highlights: Thermochemical energy storage material for storing waste heat is developed. The thermochemical energy storage material can be employed in the industrial sector. The effect of particle size of the precursor calcium carbonate was clarified. Abstract: Calcium oxide/water reaction is a promising thermochemical energy storage system owing to its high reaction enthalpy, wide availability at low cost, and favorable reaction temperature. In this research work, a calcium carbonate material was developed, featuring nano-order diameter with a silane coupling agent on the surface, and was kinetically evaluated for use in calcium oxide/water thermochemical energy storage. The kinetics analysis of the material was conducted and compared with other conventional calcium carbonate materials in which particle diameter was 2–3 μm as a reference material. Calcium oxide materials prepared through a decarbonation of calcium dioxide were used for 20 repeated cycle operations. In comparison with the conventional calcium carbonate material, the developed material showed high durability for the cycle operation and maintained its reaction conversion as almost 100% between the 8th and 20th cycle. The presence of silicate produced from the thermal decomposition of the silane coupling agent on the material surface could prevent particle aggregation. It maintained vapor diffusivity between the particles, and enhanced cyclic reaction durability of the developed material. The reaction conversion directly affects thermochemical energy storage performance, and these results indicated that the developed material had sufficient performance compared to conventional calcium carbonate materials as a thermochemical energy storage material.